The Religious Values in Literature and Their Relevance to Literature Learning in High School - Mutmainnah, Nur; Azis, Sitti Aida; Rahim, Abd Rahman (Edumaspul: Jurnal Pendidikan, 2022)
This study seeks to examine literary works which are the result of ideas which are then poured into form. Literary work itself is divided into three, namely poetry, prose fiction and drama. In this study, the researcher focuses more on prose fiction, namely the novel. This research is a qualitative descriptive study that aims to describe the Religious Values ​​in the Novel Dalam Mihrab Cinta and Bumi Cinta by Habiburahman El Shirazy. The data in this study are written data,namely in the form of quotes (words, phrases, and sentences) that show religious values ​​in the novel Dalam Mihrab Cinta and Bumi Cinta.The data source in this study is the Novel Dalam Mihrab Cinta and Bumi Cinta by Habiburahman El Shirazy. Data collection techniques are library techniques, recording techniques, and outlining techniques. The analysis technique used is. the description stage, the classification stage, the analysis stage, the relevance stage, and the conclusion drawing stage. The results in this study found (1) religious values ​​in the novel Dalam Mihrab Cinta and Bumi Cinta found values, namely, (a) Human Relationships with God (b) Human Relationships with Humans. (c) Human relationship with Nature. (2) The religious values ​​found in the novel Dalam Mihrab Cinta and Bumi Cinta are then relevant to literary learning in high school.